A STUDY OF ACADEMIC AND INDUSTRY READY-TO-WEAR FASHION PRODUCT COLLABORATION BASED ON DESIGN THINKING METHOD - Marini Yunita Tanzil; Astrid Astrid; Paulina Tjandrawibawa; Yoanita Tahalele; Fabio Ricardo Toreh (Ide dan Dialog Desain Indonesia (Idealog), 2021)
Nowadays, ready-to-wear clothing is on high demand. The suitable design for this segment will provide a design solution with good aesthetics and at the same time it will lead to business sustainability. This study aims to describe the collaboration of academics and industry to produce ready-to-wear fashion design. The research method is an experiment in the design phase to create a brand that can be accepted by the target market in collaboration with educational institutions and the garment or textile industry. Through the design thinking phases, the design process with ready-to-wear objects that last for approximately 6 months with designing the fashion business phase with the stakeholders which is simultaneous with the fashion design phase. Work review from both the experts and the users have been included in the design process. The study result demonstrates the read-to-wear design concepts, the design applications, and the business concepts along with complementary brand collateral. In focus, the design for the ready-to-wear collection has produced design concepts in twelve looks, as well as various brand collateral implementations related to the fashion business. Keyword: fashion design, ready-to-wear, fashion brand, academic and industry collaboration